"A change in perspective": Exploring the experiences of adolescents with hereditary tumor predisposition. Issue 1 (11th September 2018) - Weber, Evan; Shuman, Cheryl; Wasserman, Jonathan D.; Barrera, Maru; Patenaude, Andrea F.; Fung, Karen; Chitayat, David; Malkin, David; Druker, Harriet
Abstract: Background: Hereditary tumor predisposition syndromes (HTPSs) are being recognized more frequently in the etiology of pediatric cancer. Previous research indicates that disclosure of tumor susceptibility is a significant event in adolescents' lives. Insight into adolescents' adjustment to knowledge of their syndromes can guide healthcare delivery, particularly genetic counseling. This study explored the experiences of adolescents with hereditary tumor predisposition and their perceptions of living at risk. Methods: Seven adolescents, ages 14 to 17, representing six different childhood‐onset HTPSs, were purposively sampled and interviewed using a study‐specific semistructured interview guide. We explored the disclosure process, support systems, and the perceived benefits and harms of knowledge of hereditary tumor susceptibility. Interview transcripts were analyzed via interpretive description. Results: Three major themes emerged from the data: (1) The benefits of knowledge outweigh the harms; (2) context surrounding genetic testing must be recognized; and (3) self‐concept is influenced but not defined by tumor risk. Conclusions: We conclude that adolescents recognize the challenges associated with awareness of tumor predisposition but may also identify positive aspects in their experiences, reflecting a changed life perspective. Results of this exploratory study suggest strategies that can guide pretest and posttest genetic counseling of adolescents for HTPSs, facilitating the adaptive incorporation of genetic information into an adolescent's self‐concept.